44 Palliative simulation for internal medicine trainees (PALL-SIM-IM): a nationally adopted education initiative in response to shape of training. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Howorth, Kate; Waterfield, Kerry; Dewhurst, Felicity; Kavanagh, Emily; Brown, Jo; Billett, Hannah; Fleming, Elizabeth; Kiltie, Rachel; Woods, Elizabeth; Rowley, Grace; Charles, Max; Huggin, Amy; et al.
Abstract : Background: Shape of Training represents a significant change in postgraduate-medical-education. Internal Medicine trainees (IMT) must prove competency in 8 Clinical Capabilities in Practice (CiPs). CiP 8 Managing End-of-Life and Applying Palliative Care Skills represents an opportunity to improve palliative medicine education for generalists, however, the provision of the required education and training is also a significant challenge requiring consideration and innovation. Simulation has been recognised by the Joint Royal College of Physicians Training Board (JRCPTB) as a holistic teaching and assessment method. Aim: To produce a simulation training package for IMTs covering all components/descriptors of CiP 8 which can be effectively delivered by a combination of Palliative Medicine Trainees (PMTs), consultants, simulation technicians and teaching fellows. To enable IMTs to learn/practice required skills whilst PMTs address teaching and management curriculum competencies. Methods: The North East Palliative Registrars Research Alliance (NEPRRA) (a unique initiative ensuring all North East PMTs are involved in teaching/research projects) received simulation training and designed Palliative Simulation for Internal Medicine Trainees (PALL-SIM-IM) a package comprising scenarios mapped to IMT curriculum descriptors. Modification occurred based on feedback and new scenarios incorporated requirements unique to the COVID-19 pandemic. Results: PALL-SIM-IM has been effectively piloted in 6 sessions throughout the North-East, training 25 IMTs/equivalent. It has received excellent qualitative feedback. Quantitative data demonstrates significant improvement in competence in all curriculum descriptors following training. PALL-SIM-IM has been presented (on request) to IM Specialist Trainee Committees, Health Education England and the JRCPTB. PALL-SIM-IM has been requested by, distributed to and is to be adopted by 7 Health Education England training regions, Scotland and Northern Ireland. Conclusions: This educational initiative has successfully produced a nationally adopted simulation-based training package for IMTs to aid competency development in CiP 8, reducing duplication of work whilst allowing reciprocal development of PMTs' leadership and teaching skills.